1980
DOI: 10.1038/bjc.1980.310
|View full text |Cite
|
Sign up to set email alerts
|

Malignant properties and DNA content of daughter clones from a mouse fibrosarcoma: differentiation between malignant properties

Abstract: Summary.-Freshly isolated clones of high cloning efficiency from a mouse fibrosarcoma were examined for DNA content, cell size, protein content, and malignant characteristics such as artificial lung-colony-forming ability, s.c. tumour take, host survival, and spontaneous metastatic ability.These malignant characteristics and other cell properties were heterogeneous among these clones; the malignant characteristics could vary and were not "all or none" in their nature. The higher the DNA content or the larger t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
2

Year Published

1982
1982
1990
1990

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
7
2
Order By: Relevance
“…Thus the observed differences in the decay curves produced by the RIF-1 clones, most likely reflect the different capacities of the RIF-1 clones to become arrested in the lungs, to extravasate capillary endothelia and to survive in the surrounding lung tissue. In contrast to other findings (Suzuki et al, 1980), our observations that both cell retention in the lung and lung colonizing ability are independent of ploidy and of cell size, indicates that mechanical factors alone are not responsible for the metastatic ability of individual RIF-1 clones.…”
Section: Metastatic Ability Of Rif-j Clonescontrasting
confidence: 99%
“…Thus the observed differences in the decay curves produced by the RIF-1 clones, most likely reflect the different capacities of the RIF-1 clones to become arrested in the lungs, to extravasate capillary endothelia and to survive in the surrounding lung tissue. In contrast to other findings (Suzuki et al, 1980), our observations that both cell retention in the lung and lung colonizing ability are independent of ploidy and of cell size, indicates that mechanical factors alone are not responsible for the metastatic ability of individual RIF-1 clones.…”
Section: Metastatic Ability Of Rif-j Clonescontrasting
confidence: 99%
“…Thus, in the FSA cell clone system, selection processes for cells with higher lung colonizing potential clearly exist for "artificial" metastasis, but such selection processes cannot be demonstrated in spontaneous metastasis from leg tumours. In previous studies (Suzuki et al, 1980), more efficient dissemination of FSA1231 compared with FSA1233 was observed by measuring SLME at different times after i.m. inoculation of these tumour cells in the leg.…”
Section: Testfor Variant Selectionmentioning
confidence: 93%
“…The cell clones have been characterized regarding their malignant and related properties 1979;Suzuki et al, , 1980 Spontaneous lung metastasis efficiency (SLME) determination For determination of SLME, 106 cells were inoculated i.m. into the hind leg of each syngeneic C3H/HeJ mouse (male, 9-11 weeks old; purchased from The Jackson Laboratories, Bar Harbor, Maine).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations